Закономерности распределения электрического поля в диэлектрической среде при изменении размеров и формы проводящих включений - Щерба, М.А. (Технічна електродинаміка, 2012)
The inhomogeneous low frequency electric field distribution in dielectric medium with heterogeneous conducting inclusion simple and complex forms has been discovered. The patterns of an electric field local intensifications near such inclusion have been determined. The influence of complex form inclusions dimensional parameters on the maximal local field intensification has been proved.